Analysis of Digital Bank Usage Among Engineering Students: Case Study at Diponegoro University - Bintang Timur; Muntaromah; Indana Zulfa; Andika Firman Yudistira; Muhammad Iqbal; Nurul Haqqi Haqqoni Ismail (Department of Islamic Banking, 2025)
Purpose– This study aims to analyze the level of digital banking usage among students of the Faculty of Engineering at Diponegoro University and to identify the key factors influencing their adoption. Methodology— This study employs a quantitative approach, utilizing a binary logistic regression analysis method to analyze data collected through questionnaires from 15 respondents. Findings – The results of the analysis indicate that the overall regression model is not significant in predicting the use of digital banks, with a significance value of 0.922 and a Nagelkerke R-squared value of 0.213. However, the model is considered quite appropriate to the actual data based on the Hosmer and Lemeshow goodness-of-fit test. Of the seven predictor variables tested, only two variables have a significant effect, namely monthly pocket money, which shows a negative impact, and ICT literacy, which shows a positive effect on the use of digital banks. Implications – This finding confirms the importance of economic factors and digital literacy in encouraging the adoption of financial technology among engineering students. It supports the relevance of the Technology Acceptance Model framework in understanding the behavior of adopting digital banking services. Originality—This disciplinary focus offers novel contributions by revealing how engineering education influences the relative impact of financial capability, digital competence, and enabling conditions on the adoption of digital banking.